2013
DOI: 10.3390/molecules18010859
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of de Novo Designed L5K5W Model Peptide Isomers with Potent Antimicrobial and Varied Hemolytic Activities

Abstract: In an effort to develop short antimicrobial peptides with simple amino acid compositions, we generated a series of undecapeptide isomers having the L5K5W formula. Amino acid sequences were designed to be perfectly amphipathic when folded into a helical conformation by converging leucines onto one side and lysines onto the other side of the helical axis. The single tryptophans, whose positions were varied in the primary structures, were located commonly at the critical amphipathic interface in the helical wheel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…It was found that a Val to Lys substitution in the center of the non-polar face of a 26-residue amphipathic α-helical AMP effectively reduced the overall hydrophobicity by disrupting the continuous hydrophobic surface into 2 regions and decreased peptide self-association in aqueous solution to permit a higher degree of association with the prokaryotic cell membranes. Other studies have also found that the appropriate positioning of Trp residue(s) at the hydrophobic-hydrophilic interface of the helical wheel projection could provide an effective strategy to enhance helical stability and also increase the partitioning or penetration of designed AMPs into microbial membrane lipid bilayers with minimal effects on mammalian cell membranes or their mimics at concentrations required for antimicrobial activities [56,58,59]. Although α-helical AMPs represent the most widely investigated class of AMPs, other types of secondary structures such as β-sheets [43,60] and β-hairpin-like AMPs [61,62] have also been designed and evaluated.…”
Section: Structurementioning
confidence: 98%
“…It was found that a Val to Lys substitution in the center of the non-polar face of a 26-residue amphipathic α-helical AMP effectively reduced the overall hydrophobicity by disrupting the continuous hydrophobic surface into 2 regions and decreased peptide self-association in aqueous solution to permit a higher degree of association with the prokaryotic cell membranes. Other studies have also found that the appropriate positioning of Trp residue(s) at the hydrophobic-hydrophilic interface of the helical wheel projection could provide an effective strategy to enhance helical stability and also increase the partitioning or penetration of designed AMPs into microbial membrane lipid bilayers with minimal effects on mammalian cell membranes or their mimics at concentrations required for antimicrobial activities [56,58,59]. Although α-helical AMPs represent the most widely investigated class of AMPs, other types of secondary structures such as β-sheets [43,60] and β-hairpin-like AMPs [61,62] have also been designed and evaluated.…”
Section: Structurementioning
confidence: 98%
“…The balance between antimicrobial and hemolytic effects has been discussed in numerous works [116,[140][141][142][143][144][145][146][147][148][149][150][151]. The hemolytic effect is especially pronounced for Ltc 2a (Table 4).…”
Section: Hemolysismentioning
confidence: 99%
“…Thus, we propose that our WALK11 peptides, which show both antimicrobial and anti-inflammatory activities, are promising molecules for the development of therapies for infectious inflammation. In addition, as suggested previously [8,9], the properties of these rationally designed WALK11 peptides (i.e., their short length and simple amino acid composition) could be regarded as favorable for reducing manufacturing costs and facilitating pharmaceutical optimization for pharmaceutical and/or industrial production of bioactive peptide agents. …”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, WALK11 peptide isomers (refer to the amino acid sequences in Fig 1A) exhibited quite variable hemolytic activities against human erythrocytes, although their antimicrobial potencies were similar [8]. Thus, prior to investigating the anti-inflammatory potential of the peptides, we performed an MTT assay to assess their cytotoxicity against RAW264.7 macrophage cells.…”
Section: Initial Screening Of Anti-inflammatory Potentialmentioning
confidence: 99%
See 1 more Smart Citation